Cross-linked chitosan-sago composite membrane for direct methanol fuel cell application - Padiel, H. (Universiti Malaysia Sarawak, UNIMAS, 2010)
Fuel cell is an electro chemical device that combines hydrogen and oxygen to utilize electricity and produce water and heat. Direct Methanol Fuel Cells (DMFCs) is one of the potential portable fuel cells mechanisms. The performance of the DMFC is depending on the Proton Exchange Membrane (PEM) technology. The research and studies in improving the performance of PEM used inside the DMFC has long developed. Few factors are still hindering the existing PEM. For example, Nafion 117 has high methanol crossover, expensive, unrecyclable and short lifespan. A good PEM should has high proton conductivity, high water uptake, less swelling, low methanol permeability and crossover, and contribute to a relatively high efficiency. The fabrications of new composite samples such as chitosan – sago composite membrane, were developed and compared towards the existing composite membrane, Nafion 117. Experiments were conducted to determine the water uptake of the chitosan – sago composite membrane, the methanol permeability, conductivity of the composite membrane and the efficiency of each composite sample. 10 composite membrane samples were prepared, 5 without cross-linked and another 5 vice versa. The reason for cross-linked is to improve the hydrophilic properties of the PEM itself. Major outcome of the results in this study should satisfy all the PEM properties as mentioned above. To conclude, one sample was then suggested as the most feasible composite membrane that can be applied on the mini DMFC application.